(3eNJUQ JaSjQ GHf SdGe CHj RcQjG jMji GdJjeis - (3CHh YHO Gddg eMeO Hf YHO Gddg Hf YjSi GdeQj, GHf CHj Refjf,J (B399 (3g` s
(3ChdgG (B:s
(3bGd CHh YeQ (B: (3obQjA Ydi CHj YHO Gddg CHj Refjf GdMeO ddg GdPi CfRd GdcJGH Ydi eMeO YHO g hQShdg djchf GdYdejf fPjQkG s
(3BNQgG (B:s
(3GdPi jhShS ai UOhQ GdfGS ef GdLfI (B: (3bGd eMeO (B: (3jafi GdPi gh ef GdLf bhdg (B: (3hGdfGS (B: (3bGd jMji (B: (3hef TQ TjGWjf GdEfS Je GdLRA GdYGTQ hHg ced LejY GdOjhGf s
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B227s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eYGQVI Ydi fSNI GdeDpqdas
Keywords: (3GdJaSjQ hYdhe GdbQBfs